An Evaluation of Characters for the Separation of Two Culex Species (Diptera: Culicidae) Based on Material From the Upper Midwest. Issue 6 (4th November 2020) - Ferreira-de-Freitas, Lílian; Thrun, Nicholas B; Tucker, Bradley J; Melidosian, Lauren; Bartholomay, Lyric C
Abstract: Mosquitoes (Diptera: Culicidae) in the Culex pipiens complex play a key role in the transmission and therefore epidemiology of a number of human and animal pathogens globally. These mosquitoes, and sympatric species of the genus Culex Linnaeus that are not within the Cx. pipiens complex, are often considered 'impossible' to distinguish by morphology in the adult female stage. In the United States, this is particularly true for Culex pipiens s.l. and Culex restuans Theobald, both of which are competent vectors of West Nile virus, but likely play different roles in the transmission cycle. Therefore, we undertook an in-depth morphological evaluation of matched larval exuviae and adult specimens that revealed five useful morphological characters that are informative to distinguish Cx. pipiens s.l. from Cx. restuans in the adult stage. Herein, we provide a comprehensive review of the literature on these species of interest, and four additional, morphologically similar, Culex species, and a proposed key to adult female specimens.